Industrial policy 2005 of Bangladesh: a critical analysis of achievements and challenges - Islam, Muhammad Rafiqul (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2008.